2021
DOI: 10.1158/0008-5472.can-20-2799
|View full text |Cite
|
Sign up to set email alerts
|

Pronociceptive Roles of Schwann Cell–Derived Galectin-3 in Taxane-Induced Peripheral Neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a severe dose-limiting side effect of taxanes such as paclitaxel and docetaxel. Despite the high medical needs, insufficient understanding of the complex mechanism underlying CIPN pathogenesis precludes any endorsed causal therapy to prevent or relieve CIPN. In this study, we report that elevation of plasma galectin-3 level is a pathologic change common to both patients with taxane-treated breast cancer with CIPN and a mouse model of taxane-related CIPN. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Transcripts associated with inflammation, cytokine signaling, MAPK pathway, and transcription factors were enriched in our analysis. Utilizing established single-cell DRG RNA-seq datasets, it is likely that these transcripts originate from macrophages and Schwann cells, both of which release cytokines and chemokines and are implicated in the pathogenesis of pain [41][42][43]. This is consistent with previous work demonstrating that depletion of myeloid cells (including macrophages) alleviates postoperative pain hypersensitivity [43].…”
Section: Plos Onesupporting
confidence: 83%
“…Transcripts associated with inflammation, cytokine signaling, MAPK pathway, and transcription factors were enriched in our analysis. Utilizing established single-cell DRG RNA-seq datasets, it is likely that these transcripts originate from macrophages and Schwann cells, both of which release cytokines and chemokines and are implicated in the pathogenesis of pain [41][42][43]. This is consistent with previous work demonstrating that depletion of myeloid cells (including macrophages) alleviates postoperative pain hypersensitivity [43].…”
Section: Plos Onesupporting
confidence: 83%
“…However, the level of Gal-3 in studied patients constituted 5450.0 [4080.0; 9900.0] ng/mL and did not differ significantly from the group of healthy volunteers (4660.0 [3240.0; 6380.0] ng/mL) with p = 0.26. Based on the presented data from Koyanagi et al (2021), we expected to detect changes in galectin-3 in patients in the group with CPIN symptoms [ 52 ]. However, the level of gal-3 in this group was 5090.0 [4070.0; 8760.0] ng/mL and did not differ significantly from the level of this marker in patients without spinal symptoms (6340.0 [4620.0; 9900.0] ng/mL) and in healthy volunteers (4660.0 [3240.0; 6380.0] ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that inhibition of Gal-3 can suppress neuroinflammation, alleviate neuropathic pain caused by damage to peripheral nerves, and accelerate the recovery of nervous tissue [ 51 ]. Koyanagi et al hypothesized that Schwann cell galectin-3, released into the extracellular compartment, could be involved in the pathogenesis of CIPN by dedifferentiation and mitochondrial dysfunction, particularly following the chemotherapy with the taxane group agents [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the stimulator of interferon genes-interferon type I (STING-IFN-I) signaling axis was recognized as a critical regulator of physiological nociception and a promising target for treating CIPN [44]. Galactin-3 released by Schwann cells was also reported as a critical factor to cause CIPN [45].…”
Section: The Current Understanding Of Cipn: the Pathophysiology And Molecular Mechanismsmentioning
confidence: 99%